Functional and idling rotatory motion within F(1)-ATPase - Sabbert, D. (The National Academy of Sciences of the USA, 1997)
ATP synthase mediates proton flow through its membrane portion, F(0), which drives the synthesis of ATP in its headpiece, F(1). The F(1)-portion contains a hexagonal array of three subunits α and three β encircling a central subunit γ, that in turn interacts with a smaller ɛ and with F(0). Recently we reported that the application of polarized absorption recovery after photobleaching showed the ATP-driven rotation of γ over at least two, if not three, β. Here we extend probes of such rotation aided by a new theory for assessing continuous versus stepped, Brownian versus unidirectional molecular motion. The observed relaxation of the absorption anisotropy is fully compatible with a unidirectional and stepping rotation of γ over three equidistantly spaced angular positions in the hexagon formed by the alternating subunits α and β. The results strongly support a rotational catalysis with equal participation of all three catalytic sites. In addition we report a limited rotation of γ without added nucleotides, perhaps idling and of Brownian nature, that covers only a narrow angular domain.